20‐3: High Efficiency Wire Grid Polarizer for Quantum Dot Color Filter LCD. Issue 1 (29th May 2019) - Liu, Yujie; Zhang, Shiyu; Shi, Ge; Niu, Haijun; Fang, Zheng; Yang, Song; Han, Jiahui; Wang, Yuyao; Sun, Yanliu; IM, Yunsik; Chen, Xiaochuan; Zhu, Ming
Abstract : In quantum dot color filter (QDCF) LCD blue backlight is converted to red/green light separately by red/green quantum dot materials. In cell polarizer is necessary due to the depolarization of quantum dot material. WGP is more promising as in cell polarizer. Therefore it is particularly important to insure the transmittance of blue light as high as possible. In the article, the stacks of WGP and the upper and lower layers were designed to improve the transmittance of blue light. WGP with the upper and lower layers by chemical vapor deposition was fabricated by using nano‐imprinting lithography. The blue light transmittance of WGP in the panel without the upper and lower layers was about 24%. We optimized the design of thin film without changing the structure of WGP to make the transmittance to be increased to 40%. Experimental results showed that the proposed design could achieve a fairly high transmittance 39%.